Graft survival in South African renal transplant patients during the transition period at Charlotte Maxeke Johannesburg Academic Hospital (graft-sat study) - Chhiba, Priya Darshani (My University, 2020)
Introduction: In the developed world, studies performed on the transition of adolescent renal transplant patients have noted high rates of rejection, non-adherence and graft loss. However, there is paucity of data in developing countries, and none in a South African setting. Objectives: The purpose of this study was to assess the rates of acute and chronic rejection, graft and patient survival in adolescents at Charlotte Maxeke Johannesburg Academic Hospital (CMJAH). Methods:This study was a retrospective analysis of patients who received a renal transplant from 1 January 1990 to 31 December 2010, in the Paediatric Nephrology Department at CMJAH, in Parktown, Johannesburg, and entered the adolescent period (10 to 19 years old) with a functioning graft. Patients were included whether or not they were transferred to the Adult Nephrology Department at CMJAH.Results: 162 recipients were patients were transplanted during the study period, of which 80 (49.4%) were of black race, 63 (38.9%) were white, 10 (6.2%) were Asian and 9 (5.5%) were of mixed race. 65 (40.1%) were female and 97 (59.9%) were male. The median age at transplant was 13.8 years old (Interquartile range (IQR): 10.6 to 15.9). One hundred, twenty-eight (79.0%) patients received a renal transplant during the adolescent period and 34 (21.0%) were transplanted prior to adolescence. Fifty-four (33.3%) patients were transferred to the adult unit during adolescence. Graft failure occurred in 60 (37.0%) of the patients during the adolescent period, of which 54 (90.0%) occurred in the paediatric unit and 6 (10.0%) occurred in the adult unit. The median age at graft failure in the adolescent period was 16.1 years old (IQR: 14.5 to 17.9). Kaplan-Meier curves were used to analyse graft and patient survival. The following factors were identified as statistically significant in contributing to graft failure: if the transplant occurred during adolescence, previous renal transplant,non-compliance and rejection episodes in the adult unit, (p value <0.05). The 1, 3, 5, and 10-year patient survival rates were 98.8%, 97.6%, 95.1% and 93.9% respectively. Conclusion: This study revealed high rates of graft rejection and loss in South African renal transplant recipients in the adolescent period highlighting the vulnerability of this population group. Consideration should be given to the creation of transition clinics to potentially improve the graft outcomes of this vulnerable group. Further studies are needed on the transition period of adolescent renal transplant patients.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in the Department of Paediatrics and Child Health to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020